2018
DOI: 10.1111/pin.12685
|View full text |Cite
|
Sign up to set email alerts
|

SOX4, an epithelial–mesenchymal transition inducer, transactivates ADAM28 gene expression and co‐localizes with ADAM28 at the invasive front of human breast and lung carcinomas

Abstract: ADAM28 (a disintegrin and metalloproteinase 28) is abundantly expressed by carcinoma cells in the human breast and non-small cell lung carcinomas, and plays a role in carcinoma cell growth and metastasis. Although Src is an inducer of ADAM28 gene expression through the PI3K/AKT/mTOR and MEK/ERK pathways, direct transcriptional regulators for ADAM28 gene expression remain unknown. In this study, we performed the luciferase reporter assay and found that SOX4 (SRY-related HMG-box 4), an inducer of epithelial-mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…Moreover, co-localization of SOX4 and ADAM28 has been observed at the invasive front of human breast and lung carcinoma tissues. Altogether, these results demonstrate that ADAM28, which is transactivated by SOX4, promotes cell invasion of breast and lung carcinoma cells [74]. One can hypothesize that ADAM28 participates in SOX4-mediated EMT at invasive sites of tumors but the link remains to be clearly established (Fig.…”
Section: Epithelial-to-mesenchymal Transition (Emt)mentioning
confidence: 59%
See 1 more Smart Citation
“…Moreover, co-localization of SOX4 and ADAM28 has been observed at the invasive front of human breast and lung carcinoma tissues. Altogether, these results demonstrate that ADAM28, which is transactivated by SOX4, promotes cell invasion of breast and lung carcinoma cells [74]. One can hypothesize that ADAM28 participates in SOX4-mediated EMT at invasive sites of tumors but the link remains to be clearly established (Fig.…”
Section: Epithelial-to-mesenchymal Transition (Emt)mentioning
confidence: 59%
“…loss of cell polarity and cell-cell adhesion) and the transcription factor SOX4 (SRY-related HMG-box 4) is now reported as one of the master regulators of EMT [73]. Co-transfection of COS-7 cells with ADAM28 promoter construct and SOX4 expression vector indicates that SOX4 activates ADAM28 reporter gene expression via its interaction with ADAM28 promoter [74]. Overexpression of SOX4 in lung and breast carcinoma cells enhances ADAM28 expression resulting in increased tumor cells migration.…”
Section: Epithelial-to-mesenchymal Transition (Emt)mentioning
confidence: 99%
“…The cellular response to IGF is regulated by its binding to IGFBP, and the combination with IGFBP is stronger than the IGF affinity for the receptors. The biologically active IGF1 is one of the strongest growth factors in the activation of the ERK pathway, which is important for the development of CRC [14, 15]. IGFs, especially in association with obesity and insulin resistance, also have an impact on the increased risk of breast cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…SOX4 as an inducer of EMT could promote metastasis and development of cancers. 19,34 Furthermore, a number of evidences have been reported on the promoting role of SOX4 in chemoresistance in multiple cancers, including NSCLC. 20,35,36 Here we conrmed SOX4 as a target of miR-656-3p in NSCLC cells and further showed that ANRIL could regulate SOX4 expression by competitively binding miR-656-3p.…”
Section: Discussionmentioning
confidence: 99%